Bone morphogenetic proteins induce rabbit bone marrow-derived mesenchyme stem cells to differentiate into osteoblasts via BMP signals pathway. (August 2013) - Hu, Weihua; Ye, Yaping; Wang, Jiang; Zhang, Weikai; Chen, Anmin; Guo, Fengjing
Abstract Bone marrow mesenchymal stem cells (BMMSCs) are multipotent stem cells that can differentiate into different blastoderm cells in vitro. In this study, BMMSCs in rabbit bone marrow were isolated by density gradient centrifuge separation, purified and expanded in vitro. BMP-2 and FGF 2 were used for differentiation into osteoblasts, and the results demonstrated that bone morphogenetic proteins (BMPs) could affect the differential direction of the BMMSCs. PCR assays indicated that BMP signals pathway played important roles in osteoblasts differentiation of BMMSCs, and the members included BMPRI, Smad 1, Smad 5, Smad 8, Runx 2, collage type I and osteopontin. This study provides a theoretical basis and experimental evidence for the therapeutic application of BMMSCs to the treatment of bone injury.